Good Hygiene Practices and Their Prevention of Biofilms in the Food Industry - Fink, Rok. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2019)
This book highlights the importance of hygiene in the food industry with regard to biofilms, which can be found on the contact materials of various food production facilities, including bakery, brewing, seafood processing, and dairy and meat processing. Good hygiene practices in such facilities can prevent microbial niches and harbourage sites, facilitate cleaning and disinfection, maintain or increase product shelf-life, and improve food safety. This book provides essential information on the updated information on biofilm growth conditions, detection methods, and prevention and control strat.
Includes bibliographical references and index.
Online resource; title from PDF file page (EBSCO, viewed July 23, 2019).
Keywords: Biofilms; Disinfection and disinfectants; Food -- Safety measures; Nosocomial infections -- Prevention; Biofilms; Disinfection and disinfectants; Food -- Safety measures; Nosocomial infections -- Prevention; Electronic books; Electronic books